Digital recordings of a clinical encounter facilitate reflection in physical therapy students and clinicians - Kinney, Anthony; Nordon-Craft, Amy; Kardong-Edgren, Suzan; Kumar, Anshul; Thompson, Anne (Frontiers in Medicine, 2025)
BackgroundMedical and health professions students use digital media in their educational pursuits. No studies have examined the process or utility of reviewing digital recordings of a clinical encounter. This pilot study examined how physical therapy students varied in their approach when compared to practicing physical therapists, in their self-reflection and assessment of a recorded physical therapist (PT) encounter with a standardized patient (SP).MethodsA single site, cross-sectional, mixed-methods design was used. Participants reviewed an 11-minute digital recording of a patient encounter and completed survey questions. Post-survey interview sessions were used to gain additional perspective from participants.ResultsNinety-two physical therapy students across three levels of training and twenty-seven physical therapists participated in the study. Self-ratings of perceived clinical ability increased with each year of training. First-year students (PY1) gave higher performance ratings to the PT than other groups. Seventy-five percent of respondents found the review of the digital recording to be a useful tool for reflection. A variety of approaches in the review process were found across groups, especially between clinicians and students.ConclusionReview of a recording of a physical therapist’s encounter with an SP can be a useful educational tool for reflection across training levels of students and clinicians.